Análisis del papel de las mujeres en la investigación contable del Departamento del Quindío desde una perspectiva de género (2017)
This research project was built with the purpose of encouraging the discussion about gender in the different professional settings, aiming at expanding the field of action of accounting, including in these the contributions offered by feminist theories of the different social human and natural disciplines. With the intention of proposing new research approaches that contribute in the construction of accounting knowledge, in response to the changes that have been experienced in this context.